PENGARUH PUPUK ORGANIK CAIR PADA PERTUMBUHAN SEMAI JELUTUNG RAWA (Dyera polyphylla MIQ. STEENIS) (Effect of Applying the Liquid Organic Fertilizer on the Growth of Dyera polyphylla Miq. Steenis Seedling) : Yudha, Christopheros, Lijan Volexius Ginting - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT The aims of this study were to determine the effects of the use of liquid organic fertilizer on the growth of jelutung rawa (Dyera polyphylla Miq. Steenis ) seedling using five different treatments, namely treatment 1 (as control), treatment 2 (10 ml), treatment 3 (20 ml), treatment 4 (30 ml) , and treatment 5 (40 ml). This research used Completely Randomized Design (RAL) analysis with observation variables on hight, number of leaf, and diameter rates. Each treatment used 5 seedlings and 3 replications. This research was conducted at the nursery in Department of Forest, Palangka Raya University, and the period was from August 25 to November 3, 2017. The results showed that the treatments had only significant effect on the rate of leaf number but no significant effect to height and diameter rate, statistically, it was obtained that the best leaf number rate was the treatment 3 (three) with dose of 20 ml, i.e 7.6 leaf in average. Keywords: Liquid organic fertilizer, growth, Dyera polyphylla Miq. Steenis